WIDOWHOOD AND CHILDCARE IN KATSINA STATE: AN ISLAMIC PERSPECTIVE - Batagarawa, Khadija Tukur; Yahaya, Atiku Garba (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
This paper presents an observational and descriptive analysis of the pattern of suffering widows and orphans in Katsina State are subjected to and the extant mechanism that permits the emergence and perpetuation of these sufferings. It defines the problem focusing on three major categories of sufferings, viz: physical, social and economic sufferings, which eventually lead to many social, physical and mental effects on both sides and the community. The paper contains a survey of some selected communities in the State and some faith-based groups striving to aide widows and orphans. The last part of the paper is an analysis from an Islamic perspective. The paper adopted qualitative survey where interviews were conducted with the aim of gathering data. The analysis raises awareness that would assist in formulating strategic socio-Islamic planning in our communities and in implementing social policies for widows and orphans' physical and psychological well-being. There are some observations, recommendations and a conclusion.